Identification of aspects and barriers to implementing branding strategies in female entrepreneurship in the city of Guayaquil based on Plithogenic Neutrosophic Vague Statistics - María Fernanda Béjar-Feijoo; Nancy Ricardo-Domínguez (Neutrosophic Sets and Systems)
Branding is one of the marketing strategies that a business must follow to contribute to its prosperity. It is not just about giving a name with a logo; it is about spreading a seal of identity that makes customers identify with the company's products. If creating a successful branding strategy in the market is difficult for any entrepreneur, this is even more difficult for women entrepreneurs. As is known in business, in the labor market, and in everyday life, women face more significant challenges than men. Added to this is the fact that Ecuador is a developing country where there are considerable financial and economic limitations when it comes to boosting a business. This paper aims to identify the aspects and barriers to consider when creating an e-learning platform to help women entrepreneurs in the city of Guayaquil launch their brands. To this end, a survey is designed to identify these aspects. To process the data statistically, we prefer to use Plithogenic Statistics, with data in the form of Neutrosophic Vague Sets. On the one hand, the Plithogenic Statistics allows us to gather probabilities for the various aspects to be considered, including economic, political, social, and other factors. Furthermore, Neutrosophic Vague data allows us to capture greater accuracy in responses and address uncertainty.